Changes in membrane plasmalogens of Clostridium pasteurianum during butanol fermentation as determined by lipidomic analysis - Kolek, Jan; Patáková, Petra; Melzoch, Karel; Sigler, Karel; Řezanka, Tomáš (PloS one, 2015)
Changes in membrane lipid composition of Clostridium pasteurianum NRRL B-598 were studied during butanol fermentation by lipidomic analysis, performed by high resolution electrospray ionization tandem mass spectrometry. The highest content of plasmalogen phospholipids correlated with the highest butanol productivity, which indicated a probable role of these compounds in the complex responses of cells toward butanol stress. A difference in the ratio of saturated to unsaturated fatty acids was found between the effect of butanol produced by the cells and butanol added to the medium. A decrease in the proportion of saturated fatty acids during conventional butanol production was observed while a rise in the content of these acids appeared when butanol was added to the culture. The largest change in total plasmalogen content was observed one hour after butanol addition i.e. at the 7th hour of cultivation. When butanol is produced by bacterial cells, then the cells are not subjected to severe stress and responded to it by relatively slowly changing the content of fatty acids and plasmalogens, while after a pulse addition of external butanol (to a final non-lethal concentration of 0.5 % v/v) the cells reacted relatively quickly (within a time span of tens of minutes) by increasing the total plasmalogen content.
Keywords: 1-Butanol; Biomass; techniky vsádkové kultivace; Plasmalogens; Membrane Lipids; n-butanol; Clostridium; membránové lipidy; biomasa; plasmalogeny; Fatty Acids; nenasycené mastné kyseliny; Batch Cell Culture Techniques; Spectrometry, Mass, Electrospray Ionization; Fatty Acids, Unsaturated; mastné kyseliny; hmotnostní spektrometrie s elektrosprejovou ionizací